Clean Energy as an Alternative: Identification of Factors Determining the Willingness of Slum Dwellers - Rummana Sherwani; Abdul Waheed; Saima Gulzar (Sir Syed University Research Journal of Engineering and Technology, 2023)
Increasing trends towards globalization and modern lifestyle are going to deplete, energy resources rapidly. Increasing trends towards energy use directly harness the environment and ecosystem of the earth, depicting that energy will be one of the most important future problems of the world. Clean and sustainable energy alternatives are required to meet this demand in order to combat the antagonistic environmental problems. Renewable energy sources have the potential to fulfill the energy gaps without affecting the ecosystem and the greenhouse gases emittance. The transformation of people causes the generation and creation of slum areas in the cities due to ever-increasing urbanization. Presently around one billion people are residing in slum areas. Most slum dwellers are found in less economically developed countries, which makes it 30% of the total population. The inhabitants of slum dwellers are more likely to be increased by two billion by 2030 and to three billion by 2050. Pakistan is facing a severe energy deficiency. The energy gap between energy supply and demand is widening with time. Limited fossil fuel resources allow the country to import nonrenewable energy resources to fill this gap. Gas connection problems and energy shortfalls compel urban households to use nonrenewable energy resources. The need of the hour is to diversify the energy resources like biogas, hydropower, solar, and wind to overcome the energy shortfall in the country. Fossil fuel usage for an energy source in households is the major cause of environmental degradation in urban households. Owed to bad smoke and insufficient ventilation, health-related problems like respiratory issues, stomach problems, and other contagious diseases are associated. The smoke that is caused by the combustion of biofuels impacts residents health badly, especially respiratory problems. The primitive aim of this research is an assessment of energy sources being used and to dig out reasons for their impacts on the health conditions of residents of slum dwellers in Pakistan stratified random sampling is used for data collection and correlation analysis was performed to find out the result.